Pengaruh DER, PBV, dan EPS Terhadap Harga Saham pada Sektor Properti - Santoso, Dewi Fortuna; Juwita, Ratna (MDP Student Conference, 2025)
The purpose of this study is to determine the effect of Debt to Equity Ratio, Price Book Value and Earnings Per Share on stock prices in property & real estate companies for the period 2015 - 2023 listed on the Indonesia Stock Exchange. The research method used in this study is a quantitative method. The sampling technique used in this study is purposive sampling and the data needed in this study were taken from the financial statements of each company with a population of 89 companies. There are 17 companies that meet the sampling criteria. The results of this study, it shows that Debt to Equity Ratio, Price Book Value and Earnings Per Share have a significant effect on stock prices